1968
DOI: 10.1136/bmj.2.5597.83
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of breast in trans-sexual individuals after surgical and hormonal interference with the primary and secondary sex characteristics.

Abstract: Whatever the forces are that drive some individuals to procure the outward physical appearance of the sex that they were not born to, the normal man and woman tend to be shocked on discovering the extent that others will go to in the search for sex metamorphosis. A sense of shock may be a natural reaction to what is described in this paper, but it should surely be tempered through pity-the two men whose cases are reported here experienced tragedy of a sort unprecedented even among such tragedy-prone people. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

1969
1969
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(58 citation statements)
references
References 0 publications
1
55
0
2
Order By: Relevance
“…Since oestrogens are heavily implicated in the promotion of breast cancer (Lacassagne, 1932;Symmers, 1968), local areas of enhanced oestrogen production might be expected to encourage development of tumour foci at these favourable sites. If this is the case one would expect a particular association between high aromatase activity in adipose tissue and oestrogen receptor positive tumours which are more likely to be oestrogen responsive.…”
Section: Discussionmentioning
confidence: 99%
“…Since oestrogens are heavily implicated in the promotion of breast cancer (Lacassagne, 1932;Symmers, 1968), local areas of enhanced oestrogen production might be expected to encourage development of tumour foci at these favourable sites. If this is the case one would expect a particular association between high aromatase activity in adipose tissue and oestrogen receptor positive tumours which are more likely to be oestrogen responsive.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature includes 15 reported cases of breast cancer in transwomen who received estrogen therapy (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Most reported cases were relatively young, with some patients presenting in their early 30s.…”
Section: Possible Effects Of Cross-sex Hormonesmentioning
confidence: 99%
“…Men with prostate cancer and transsexuals who are treated with exogenous estrogens or antiandrogens may be at higher risk of breast cancer. 29,30 A recently published Swedish paper examined male patients with both breast and prostate cancer, and suggested that most of the apparent increased risk of male breast cancer following prostate cancer was related to estrogen or antiandrogen treatment; or in small numbers, the BRCA-2 gene. 31 At least two case reports exist of transsexual males developing breast cancer after estrogen therapy.…”
Section: Non-genetic Risk Factorsmentioning
confidence: 99%